Improving compliance with advanced care planning completion for Haematology inpatients at a tertiary centre - Kaustubh Leetkar; Claire Burney (Future Healthcare Journal)
Aim: To increase the number of inpatients with a completed ‘Recommended Summary Plan for Emergency Care and Treatment (RESPECT)’ form on the Haematology ward.Rationale – Junior doctors often find themselves dealing with deteriorating patients who do not have completed RESPECT forms. All inpatients should ideally have an advanced care plan (RESPECT form) to guide treatment, especially in the event of acute deterioration. Due to the complexity of haematological disorders, junior doctors have fairly limited knowledge of the prognosis associated with specific haematological conditions and the various lines of treatment used for them, and the nuances needed in planning for treatment escalation for these patients, these decisions are best made by experienced consultants or registrars.Methodology: Prospective data collection was completed on the number of Haematology and bone marrow transplant inpatients who had a completed Respect form in the haematology wards. We found that only 38% of them had a Respect form. We shared this finding in the Haematology MDT and highlighted the need to increase this number. We discussed this with the ward nurses and requested them to flag up pending RESPECT forms during board rounds (similar to VTE assessments). We put up a poster above the patient notes cabinet, highlighting the need to complete Respect forms. We spoke to the BMT co-ordination team about including RESPECT forms in the pre-transplant assessment paperwork. We re-audited the compliance after 3 weeks. Results: On re-auditing, 76% of inpatients had RESPECT forms. We plan to re-audit in a month's time to see if this improvement is being sustained. Conclusions: We were able to find a solution to achieving a meaningful increase in compliance with RESPECT form completion due to engaging members of the MDT in the process of enacting a change and by implementing change at multiple levels so that it is a systematic, sustained change.